Criteria and indicators for sustainable plantation forestry in India - Sankar, S.; Anil, P.C.; Amruth, M. (Center for International Forestry Research, 2000)
In recent years CIFOR has developed a system for testing C&I for assessing the sustainability of management of natural forests at the level of a forest management unit (FMU). This system was used to develop C&I for teak and eucalypt plantations in two states in India. Development and evaluation of C&I was conducted by the Kerala Forest Research Institute (KFRI), Peechi, Kerala, in collaboration with the Indian Institute of Forest Management, Bhopal, in Madhya Pradesh. The project provided an opportunity for forestry scientists, forest managers, local communities, and NGOs in Kerala and Madhya Pradesh to participate in the testing and evaluation of C&I of sustainable management of plantations based on the Iterative Filtering and Generation Method (IFGM) developed for natural forests by CIFOR. Field testing in Kerala was conducted in an age series of teak plantations at Nilambur and in young eucalypt plantations of the Punalur forest district. Both FMUs were managed by the Department of Forestry in Kerala. In Madhya Pradesh field testing was conducted in teak plantations of the Raipur district managed by the Madhya Pradesh Forest Development Corporation (MPFDC). To rationalise this process it is found necessary to first group all C&I under four principles: viz. policy and planning, ecology, socio-economic and management. These were then further divided into subgroups before starting the selection process for the candidate sets for field testing. Field testing of C&I based on stage 2 of the IFGM process evolved and teams became more proficient during the two tests conducted in Kerala and the third test later on in Madhya Pradesh. The three teams defined sets of C&I, as well as verifiers for some indicators, specific to each test site. Comparison of these three sets showed that a high proportion of policy indicators proposed for teak plantations in Madhya Pradesh were unique due to differences in forest policies and organisations responsible for managing plantations in the two states. Likewise, a number of ecology indicators addressed specific local issues. A large number of socio-economic indicators were common for all sites reflecting similarity of social issues. Management issues were also similar, consistent with the historical development of plantation management in the two states. Stakeholder participation during the field tests and final workshops, including local communities and NGOs played an essential role in shaping C&I related to social and economic concerns. This raised a number of important issues including:impact of plantation development on water supplies to villages and settlements; minimum set of C&I applicable to the three sites included in this project and considered to be more widely relevant to plantation forestry across India.This evaluation also identified a number of unique C&I addressing policy, ecological and socio-economic issues of local importance. The results from this project demonstrated the importance of testing and evaluating C&I at the FMU level to ensure that local issues pertaining to the sustainable management of forest plantations are addressed. loss of biodiversity and the long-term impact on NWFP collected by local communities to supplement income; sharing of benefits from plantation development to improve opportunities for schooling, training and employment; and environmental impacts, such as soil erosion and contamination. The site-specific C&I developed by the three teams were examined for commonalities and this formed the basis for a minimum set of C&I applicable to the three sites included in this project and considered to be more widely relevant to plantation forestry across India This evaluation also identified a number of unique C&I addressing policy, ecological and socioeconomic issues of local importance. The aim of this project demonstrated the importance of testing and evaluating C&I at the FMU level to ensure that local issues pertaining to the sustainable management of forest plantations are addresed